DECISION SUPPORT SYSTEM KELAYAKAN PEMBERIAN SERTIFIKASI GURU DENGAN METODE FUZZY MULTI CRITERIA DECISION MAKING (FMCDM) PADA UPTD PENDIDIKAN KECAMATAN SINGKUT JAMBI - Novhirtamely Kahar; Irmalena - (JURNAL AKADEMIKA)
Teacher certification is the process of awarding certificates to the teacher educators who have fulfilled the requirements. In order to uphold the principles of accountability honest certification, transparent, and objective in UPTD of Singkut District Jambi, the study aims to build an application Decisi on Support System (DSS) Eligibility Provision of Teacher Certification with Fuzzy Multi Criteria Decision Making (FMCDM) Method. Applications built is expected to help the parties UPTD of Singkut District Jambi in providing teacher certification to teachers who have met the criteria. Data input to the application is based on the teacher data and the requirements data as a teacher certification criteria. While the ouput is a form of information in the form of teacher data reports deserving teacher certification. This application was built using Delphi 7.0 programming connected with the MySQL database for data storage. The results showed FMCDM method can be applied to the feasibility of providing decision support system of teacher certification in the UPTD of Singkut District Jambi. With the decision support system, the more objective the provision of teacher certification based on requirements that are owned by the teacher.